2016
DOI: 10.3171/2015.12.spine15805
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with improvement in sagittal spinal alignment after microendoscopic laminotomy in patients with lumbar spinal canal stenosis

Abstract: OBJECTIVE Little is known about the relationship between sagittal spinal alignment in patients with lumbar spinal canal stenosis (LSS) and objective findings such as spinopelvic parameters, lumbar back muscle degeneration, and clinical data. The purpose of this study was to identify the preoperative clinical and radiological factors that predict improvement in sagittal spinal alignment after decompressive surgery in patients with LSS. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…Of 18 studies, three failed to produce the data needed for the meta-synthesis [27][28][29]. Thus, the quantitative meta-analysis was performed on 15 studies [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. LSS had been used as an inclusion criterion in 15 studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 18 studies, three failed to produce the data needed for the meta-synthesis [27][28][29]. Thus, the quantitative meta-analysis was performed on 15 studies [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]. LSS had been used as an inclusion criterion in 15 studies.…”
Section: Resultsmentioning
confidence: 99%
“…A single previous systematic review of the topic, which included 10 studies (eight of which were included in our review) [57], while lacking a quantitative meta-analysis, estimated that decompression surgery led to SVA correction in 25% to 73% of patients. It has also been suggested that greater PI-LL preoperatively correlates with residual sagittal malalignment postoperatively, which could be explained by structural degenerative changes rather than by reversible changes due to LSS itself [33,34,40].…”
Section: Discussionmentioning
confidence: 99%
“…Most studies 9–74 used conventional MRI for measuring FI. In the field of MRI sequence, our results showed that T2‐weighted images 10,12–14,17,18,20,24,25,27,29,30,32–35,37,39–53,55,56,58–63,65,66,69,70 were used in quantitative assessments more often. It is expedient for orthopaedists to evaluate FI on frequently‐used T2‐weighted images.…”
Section: Literature Reviewmentioning
confidence: 99%
“…1,2 Several studies on improved sagittal alignment after decompression alone in lumbar spinal stenosis (LSS) patients were recently published. [3][4][5] We also reported previously on the relation between preoperative sagittal imbalance and LBP before and after decompression surgery in LSS patients. 6 Degenerative spondylolisthesis (DS), when lumbar vertebrae slip forward onto lower vertebral bodies, is also associated with spinopelvic sagittal imbalance.…”
Section: Introductionmentioning
confidence: 70%